Improving Waste Management and Maggot Cultivation Capabilities at Pondok Pesantren As Salafy Al Asror Semarang - Fachrurrozie; Martono, S; Nurkhin, Ahmad; Mukhibad, Hasan; Kardoyo (Indonesian Journal of Devotion and Empowerment, 2024)
Pondok pesantren are educational institutions that are expected to contribute to environmental education, especially in overcoming the waste problems. A survey by the FEB UNNES Service Team regarding waste management at the Pondok Pesantren As Salafy Al Asror showed several problems in waste management, including not yet optimal management of temporary waste, and processing of organic waste that has the potential to be reprocessed. The implementation method is training and coaching. Training methods are implemented through waste management training for cleaning teams and santri and maggot cultivation training as well as providing adequate work safety equipment. The service activity was carried out on May 18 2024 at Al Asror Vocational School with 20 male students and 10 surrounding residents. The speakers for the activity were the service team leader, kiai, and practitioners from the Semarang City Zero Waste Community (Komunals). The activity was carried out in the form of training with two material sessions, namely waste management and maggot cultivation. The activity was opened by the cottage caretaker, KH. Al Mamnuhin Kholid. The first material was delivered by Drs. Fachrurrozie, M.Si. which emphasizes the importance of managing waste so that it can have a positive impact on the surrounding environment. The second material was delivered by Dr. Inaya Sari Melati, M.Pd. and Luthfan Faladias. Based on the results of the pre-test and post-test that have been carried out, it can be stated that there has been a significant increase in participants' knowledge in waste management and maggot cultivation.